ANALISIS PENERAPAN KESELAMATAN KERJA DALAM UPAYA PENGENDALIAN KECELAKAAN KERJA DI PT. BUDI DWIYASA PERKASA - Farah Alhamid (Fakultas Teknik Universitas Tulang Bawang Lampung, 2017)
In conducting activities, many found workers who did not use personal protective equipment, do not pay attention to safety in work and work done like without procedure. PT. Budi Dwiyasa Perkasais a plantation company palm oil. Based on accident data obtained work, there are 14 case of accident in April until June 2016 in PT. Budi Dwiyasa Perkasa. A major factor cause of the accident is unsafe actions and unsafe conditions. Hazard analysis needs to be done in order to prevent the accident of work. Hazard identification done with using the risk assessment method. This analysis of the technique used to determine the level of the risk of a job is a combination of between the possibility of the harms caused by the severity of the caused. The result of hazard identification with this method is used in a kind of work to have a high risk level and need to address special in order to prevent the accident.